2016
DOI: 10.1161/atvbaha.116.307847
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Proneurotensin Concentrations and Cardiovascular Disease Events in the Community

Abstract: Objective Neurotensin is a peptide whose receptor (SORT1) is linked to cardiovascular disease (CVD) development. We hypothesized concentrations of pro-neurotensin (pro-NT; stable pro-fragment of neurotensin) would predict incident CV events in community-based subjects. Approach and Results Blood samples from 3439 participants in the Framingham Heart Study (FHS) Offspring cohort (mean age 59.2 years, 47.1% male) were tested for pro-NT. Primary outcome of interest was incident hard CVD (myocardial infarction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 14 publications
5
56
1
Order By: Relevance
“…This association between serum pro-NT levels and CAD development was lately confirmed in 4804 elderly participants from the Malmö Preventive Project (MPP) (HRs Z 1.10, 95% CI 1.06e1.54, P Z 0.037) [24]. More importantly, recent data from the cohort of the FHS Offspring showed that higher serum pro-NT levels were associated with 27% greater risk of incident cardiovascular events (HR Z 1.27, 95% CI 1.06e1.54, P Z 0.011) [25]. Our present study first observed the link between serum pro-NT levels and premature CAD risks in patients with PCAD and controls.…”
Section: Discussionmentioning
confidence: 96%
“…This association between serum pro-NT levels and CAD development was lately confirmed in 4804 elderly participants from the Malmö Preventive Project (MPP) (HRs Z 1.10, 95% CI 1.06e1.54, P Z 0.037) [24]. More importantly, recent data from the cohort of the FHS Offspring showed that higher serum pro-NT levels were associated with 27% greater risk of incident cardiovascular events (HR Z 1.27, 95% CI 1.06e1.54, P Z 0.011) [25]. Our present study first observed the link between serum pro-NT levels and premature CAD risks in patients with PCAD and controls.…”
Section: Discussionmentioning
confidence: 96%
“…Notably, the angiogenesis biomarker, vascular endothelial growth factor (VEGF), was the only biomarker that was elevated in women, which is consistent with a prior angiogenesis clinical trial that was positive only in women, and supportive of the emerging concept that female progenitor cells may act as superior regenerative therapeutics compared to progenitor cells from males [ 60 - 62 ]. Recent studies have found that plasma levels of the neurotensin precursor hormone proneurotensin predict the development of cardiovascular disease and are significantly higher in women compared to men [ 63 65 ].…”
Section: Methodsmentioning
confidence: 99%
“…Very recently, we demonstrated the existence of a positive association between NT and leptin levels in the bloodstream, which makes the hypothesis that NT modulates leptin concentration in periphery through mechanisms involving gut fat absorption more plausible [ 5 ]. Several experimental models show that NT mediates the development of fatty liver disease and obesity [ 6 , 7 , 8 ] while, in humans, large epidemiological studies demonstrate that higher circulating levels of pro-neurotensin (pro-NT), which is the stable NT precursor released in equimolar amount with NT, predict obesity, type 2 diabetes (T2D), and cardiovascular disease [ 9 , 10 ]. Obesity-associated diseases such as insulin-resistance, T2D, and metabolic syndrome (MS) have been associated with adipose tissue (AT) dysfunction occurring in conditions of chronic excessive caloric intake [ 11 ].…”
Section: Introductionmentioning
confidence: 99%